Efeito de níveis de aditivo natural à base de tanino sobre a fermentação e digestibilidade ruminal - Monteiro, Caio Rodrigues (2021)
Several natural molecules have the potential to be used as a sustainable and safe additive for ruminant feed, enabling increased productivity and reduced environmental impacts. The objective of this study to evaluate the effect of increasing doses of Acacia mearnsii condensed tannin extract (TAN): 0.00; 0.08; 0.16; 0.32 and 0.64% (diet dry matter; DM) on nutrient digestibility and ruminal parameters, with different laboratory methods. Three experiments were carried out: dual flow continuous culture system (in vitro; E1); in situ (E2) and batch culture (in vitro; E3). To obtain inoculum for E1 and E3 and incubation of E2, Nellore cattle cannulated in the rumen were used. E1 was conducted in a replicated 5x5 Latin square, with five periods of 10 days (7 of adaptation and 3 of collection). The culture was kept in anaerobic conditions at controlled temperature and diets (2 mm) were fed twice a day. E2 was conducted in a randomized 2-block design (ruminal environment), replicated in 3 periods. E3 was conducted in a randomized block design, considering the incubation period as a block. For statistical procedures, SAS PROC MIXED was used, with period, treatment and square as fixed effect and experimental unit as random effect for E1; block, treatment and period as a fixed effect for E2 and block and treatment as a fixed effect for E3. The LSMEANS statement was used to compare means, with the adjustment proposed by Tukey-Kramer for significant effects. Diets with (CT) and without (ST) tannin were compared, by CONTRAST statement, and diets with low (BT; 0.08 and 0.16%) and high (AT; 0.32 and 064%) tannin. A linear or quadratic adjustment test was performed to relate TAN dose and response variables. Significance was established at P ≤ 0.05 and trends at P < 0.10. In E1, there was no difference in crude protein digestibility (CP; P=0.07) and CT increased the digestibility of organic matter (OM; P=0.02; 51.0 vs 49.3%) and dry matter (DM; P= 0.04; 46.4 vs 45.2%), compared to ST. The pH did not differ between diets (P>0.10). The final ammonia concentration was higher with 0.16% TAN (P=0.01) and lower in diets with AT, compared to BT (0.69 vs 0.56 mg/dL; P<0.01). Isobutyrate concentration was higher at 0.08% TAN (P<0.01). Inclusion of TAN reduced total VFA (P<0.01), acetate (P<0.01), butyrate (P=0.04), valerate (P=0.03) and acetate:propionate (P<0, 05). In E2, there was a quadratic effect (P<0.02) between doses of TAN and digestibility of DM and CP. CT diets reduced the digestibility of DM (58.9 vs 54.5%; P<0.01) and CP (56.1 vs 54.4%; P=0.03), while the CP digestibility was higher for AT, compared to BT (P<0.01). In E3, there was a lower content of acetate (P<0.01) and higher of butyrate (P<0.01) when TAN was added. Addition of TAN compared to the control reduced the acetate:propiont ratio, increased the digestibility of DM and OM and did not change the pH and ammonia concentration of the medium, but reduced the total VFA and acetate.